Efektivitas Program Keluarga Harapan (PKH) dalam Meningkatkan Kesejahteraan Masyarakat di Kelurahan Bahu Malalayang Satu Kota Manado - Jericho Danga Pombengi; Joyce Jacinta Rares; Prety Wungow; Ledya Wonok; Tesalonika Mundung; Christian Mandagi (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2026)
The Family Hope Program (PKH) is a conditional social assistance policy designed to improve the welfare of poor and vulnerable households through enhanced access to education, health, and social welfare services. This study evaluates the implementation of PKH in Malalayang Satu Village, Manado City, by identifying its achievements, implementation constraints, and opportunities for improvement. The study employed a descriptive qualitative approach through a literature review of scholarly articles, books, policy documents, and other relevant secondary sources. The analysis applied a public policy evaluation perspective, focusing on effectiveness, efficiency, responsiveness, and equity. The findings indicate that PKH has contributed to meeting the basic needs of beneficiary families, particularly by supporting children’s education, access to health services, and household purchasing power. The program also provides an important social protection mechanism for families facing economic vulnerability. Nevertheless, several implementation challenges remain, including inaccuracies in beneficiary targeting, limited capacity of programme implementers, uneven transparency in aid distribution, and the tendency of some beneficiaries to use assistance primarily for short-term consumption. These conditions may limit the programme’s capacity to promote long-term economic independence. The study concludes that PKH implementation needs to be supported by more accurate and integrated beneficiary data, strengthened social assistance and monitoring, transparent complaint-handling mechanisms, and empowerment programmes linked to skills development and income-generating activities. Such measures are essential to improve programme accountability, equity, and sustainability in Malalayang Satu Village.